MICROWAVE ASSISTED SYNTHESIS OF HETEROCYCLIC COMPOUND AND ITS ANTICANCER ACTIVITY (Journal of Pharmaceutical Negative Results, 2022)
The chemistry of heterocyclic compounds has been an interesting field of study for a long time. The synthesis of novel Oxadiazole derivatives and investigation of their chemical and biological behavior have gained more importance in recent decades for biological, medical and agricultural reasons. Azole derivatives are the important class of the heterocyclic compounds. Derivatives of 1,3,4 oxadiazole 2,5 disubstituted position have been reported to possess considerable pharmacological activities. Synthesize oxadiazole with various substitution from starting material 1 hydroxy 2 -napthoicacid. 1, 3,4 oxadiazole which were synthesized in laboratory as part of an ongoing program of discovering small molecules with multiple beneficial effects in metabolic syndrome. An effective synthesis of different novel 2, 5-disubstituted- 1,3,4 oxadiazole derivatives by nucleophilic addition elimination reaction, nucleophilic substitution reaction and cyclization reaction. 1-hydroxy- 2- naphthoic acid with concentrated sulphuric acid and ethanol resulted the formation of carboxylate, and again refluxing in ethanol and hydrazine hydrate resulted the formation of carbohydrazide intermediate. when treated with cynogen bromide,1,4 diaxone and sodium bicarbonate and ethanol the formation of compound 1,3,4 oxadiazole, derivatives were synthesized by using different aromatic aldehyde. Results demonstrated that microwave method is more eco-friendly than conventional method.